ANALISIS KONDISI KESEHATAN GIGI PADA BALITA DI WILAYAH KERJA PUSKESMAS PUNDONG KABUPATEN BANTUL - Pamungkasih, Wahyu; Supatmi; Pranawati, Erna (Jurnal Riset Daerah, 2024)
Dental caries is the most common health problem among toddlers, with a high prevalence in various regions, including Indonesia. The main risk factors contributing to caries in toddlers include unhealthy diets, poor oral hygiene habits, and a lack of parental knowledge about children's dental care. This issue can significantly affect the quality of life and overall health of toddlers. This study utilized a descriptive observational design with a cross-sectional approach. The sample consisted of toddlers aged 0-5 years who visited Posyandu and Puskesmas Pundong from August 2023 to August 2024. Data were collected through clinical examinations to assess the incidence of caries and oral hygiene, as well as structured interviews with parents regarding risk factors such as diet, brushing habits, and fluoride use. Descriptive and correlational statistical analyses were used to identify relationships between risk factors and dental health conditions. The study found that 51% of toddlers experienced dental caries, with poor oral hygiene observed in 29% of them. A total of 44% of toddlers were at high risk of developing cavities. A positive correlation was found between age and the number of caries, as well as a relationship between inadequate brushing habits and high rates of caries. The main risk factors contributing to caries were high sugar consumption and infrequent tooth brushing. The prevalence of dental caries among toddlers in the Puskesmas Pundong area is notably high, with risk factors influenced by diet, oral hygiene, and parental knowledge. Early preventive interventions through parental education, regular dental visits, fluoride use, and dietary changes are needed to reduce the risk of dental caries in toddlers. A collaborative approach between healthcare professionals and parents is essential to improve toddlers' overall dental health